Association between Metabolic Syndrome and Its Components with Cardiovascular Disease Risk in the MASHAD Cohort Study Population - Zahra Asadi; Hamideh Ghazizadeh; Ameneh Timar; Mohammad Amin Khodadadegan; Hamed Ghazavi; Mohammad Nasrabadi; Toktam Sahranavard; Mohammad Reza Fazl Mashhadi; Mohammad Amin Mohammadi; Arezoo Rastegar-Moghadam; Ali Ebrahimi Dabagh; Sara Moazedi; et al. (Journal of Cardio-Thoracic Medicine)
Introduction: The primary aim of this study was to evaluate the association of metabolic syndrome (MetS), based on different definitions, with the risk of total cardiovascular disease (CVD), unstable angina (UA), stable angina (SA), and myocardial infarction (MI). Additionally, we aimed to investigate which definition of MetS is a better predictor of CVD events in a large sample of Iranian adults.Methods: The analysis was conducted among 7,910 adults from the Mashhad Stroke and Heart Atherosclerotic Disorder (MASHAD) cohort study. The presence of MetS at baseline was defined using the following criteria: International Diabetes Federation (IDF 2005), National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III), and World Health Organization (WHO). Hazard ratios (HR) and 95% confidence intervals (CI) were used to estimate the association of MetS and its components with CVD events.Results: The prevalence of MetS among CVD patients was 56.40%, 52.30%, and 23.90% based on the IDF, NCEP ATP III, and WHO criteria, respectively. The highest HR for total CVD (HR: 2.29; 95% CI: 1.54–3.40; P<0.001), UA (HR: 2.13; 95% CI: 1.22 – 3.72; P<0.01), and MI (HR: 3.11; 95% CI: 1.33–7.26; P<0.01) was found when using the WHO definition. The highest HR for SA (HR: 2.56; 95% CI: 1.37 – 4.81; P<0.001) was found when using the NCEP ATP III definition.Conclusion: Having MetS based on the WHO definition was a significant predictor for the incidence of total CVD, MI, and UA, while having MetS based on the ATP III criteria was associated with a higher risk of SA in the MASHAD study population.